2023
DOI: 10.3389/fbioe.2023.1115254
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorocarbons: A perspective of theranostic applications and challenges

Abstract: Perfluorocarbon (PFC) are biocompatible compounds, chemically and biologically inert, and lacks toxicity as oxygen carriers. PFCs nanoemulsions and nanoparticles (NPs) are highly used in diagnostic imaging and enable novel imaging technology in clinical imaging modalities to notice and image pathological and physiological alterations. Therapeutics with PFCs such as the innovative approach to preventing thrombus formation, PFC nanodroplets utilized in ultrasonic medication delivery in arthritis, or PFC-based NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…Seeking new drugs and methods to treat SD-ALI is important. Previous studies found that PFCs were effective in improving oxygenation in animals with lung injury and hypoxia, with the therapeutical effect mainly being ascribed to anti-inflammation and anti-oxidative stress effect by NF-κB pathway [18,27,28]. Our study established a SD-ALI model that fulfilled the standard for acute lung injury models updated in 2021 by the American…”
Section: Discussionmentioning
confidence: 74%
“…Seeking new drugs and methods to treat SD-ALI is important. Previous studies found that PFCs were effective in improving oxygenation in animals with lung injury and hypoxia, with the therapeutical effect mainly being ascribed to anti-inflammation and anti-oxidative stress effect by NF-κB pathway [18,27,28]. Our study established a SD-ALI model that fulfilled the standard for acute lung injury models updated in 2021 by the American…”
Section: Discussionmentioning
confidence: 74%
“…56 However, achieving vascularization within the implanted scaffold takes time, so making readily available oxygen is crucial for maintaining the metabolic demands and physiological functions of native islet cells. 54,57,58 A minimum pressure level of 40 mmHg should always be maintained within the pancreas regarding oxygen, as insufficient access poses one of the main reasons behind graft failure. 59 A macrocapsule that contains alginate hydrogel with PFOB was designed by our study for pancreatic islet transplantation, with the main purpose of providing oxygen post-transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…There are no prospective trials that show the risks of hyperoxia or methods used to reduced demand are outweighed by their benefits, However, a recent re-analysis of data from both the ICU-ROX and PILOT randomized controlled trials, suggest that using individualized oxygenation targets derived from machine Synthetic oxygen carriers (SOC) have indeed been considered in this effort, two common classes used are hemoglobin-based carriers (HBOC) and perflurocarbons (PFC). PFCs are largely being studied in the diagnostic and therapeutic realm; as carrier for oxygen for use in imaging or other interesting biologic applications, but not necessarily for cellular metabolism [65]. HBOCs have been studied as an oxygen carrier for delivery to cells for metabolism, in trauma for instance.…”
Section: Optimizing Tolerance Of Anemia In the Icumentioning
confidence: 99%